Stable prevalence of obesity among Ngāti Whātua 4-year-old children in 2010–2016. Issue 4 (2nd October 2019) - Rapata, Hannah; Cutfield, Wayne S.; Milne, Barry J.; Shackleton, Nichola; Waetford, Cathrine; Richards, Rosalina; Taylor, Rachael W.; Raureti, Terina; Derraik, José G. B.; Camp, Justine
ABSTRACT: Recent evidence indicates a slight decline in the overall prevalence of obesity in New Zealand children (including Māori), but it is unknown whether this pattern is reflected across all iwi. We examined obesity prevalence (body mass index (BMI) ≥95th percentile) among 4-year-old children of Ngāti Whātua descent ( n = 2031) enrolled in the B4 School Check from 2010 to 2016. Possible differences according to sociodemographic factors were examined. There was no evidence that obesity prevalence among Ngāti Whātua children changed throughout the study period. Mean prevalence was 21.2%, but there was marked yearly variation, ranging from 17.5% to 23.2%. Overall, mean prevalence differed according to sociodemographic factors, being higher in boys than girls (24.5% vs 17.9%) and among children from most deprived compared to least deprived households (25.5% vs 16.2%). Their overall mean BMI z -score was 0.88 (95%CI 0.84, 0.93), with sociodemographic differences mirroring those for prevalence: boys 0.99 vs girls 0.78; and most deprived 0.90 vs least deprived households 0.76. In conclusion, In contrast to national figures, obesity prevalence among Ngāti Whātua children appeared to be unchanged throughout the study period, indicating national data from the larger Māori population in New Zealand cannot be assumed to reflect the trends within individual iwi.